PERFORMANCE AND EMISSION CHARACTERISTICS OF RAPHANUS SATIVUS, JATROPHA, AND BALANITES AEGYPTIACA SEED MIXED BIODIESEL BLENDS IN A DIRECT INJECTION DIESEL ENGINE - G HIMA BINDU; ISLAVATH LOKESH NAYAK; PATHRY MANU; CH VIBHUH AAAYAN (Utilitas Mathematica, 2025)
The current study analyzes the performance and emission attributes of different blends (0%, 20%, 40%, 60%, 80%, and 100% being termed as MB0, MB20, MB40, MB60, MB80 and MB100, respectively) of biodiesel derived from Raphanus sativus, Jatropha, and Balanites aegyptiaca seeds with conventional diesel. The MB0 blend was pure diesel, and the MB100 blend was pure biodiesel (with no diesel). Critical performance parameters like Brake Thermal Efficiency (BTE), Brake Specific Fuel Consumption (BSFC), and Exhaust Gas Temperature (EGT) were evaluated experimentally. Moreover, the environmental effects were assessed by measuring emission characteristics such as Carbon Monoxide (CO), Hydrocarbons (HC), Nitrogen Oxides (NOₓ), and Smoke Opacity. The results indicated that the mixed biodiesel blend MB20 exhibited a higher BSFC by 5.08% and a lower BTE by 3.13% compared to diesel at maximum load. The emission characteristics are much better performed by MB20 when compared with diesel. Additionally, the study examined the influence of diethyl ether as an oxygenated additive on the targeted biodiesel blend. The improved biodiesel blend (MB20) was blended with 5%, 10%, and 15% DEE, and MB95E5, MB90E10, and MB85E15 were prepared. Incorporating diethyl ether dramatically changed combustion behavior. The performance and emission characteristics were substantially changed. The results are presented and discussed here.